Drug Induced Hepatotoxicity – An Ongoing Challenge - Mehr Fatima; Syed Ijaz Hussain Zaidi (Journal of Bahria University Medical and Dental College)
Drug induced liver injury is one of the main factor of liver failure and acute liver damage world wide with high incidence in western countries. Liver injury can be intrinsic (dose dependant) or idiosyncratic (dose independent). However idiosyncratic type is considered to be mainly responsible for drug induced liver damage. Binding of reactive metabolites of drugs to tissue proteins and oxidative stress is the possible cellular mechanism involved in this process. Moreover, some antibiotics, anti-epileptics, nonsteroidal anti-inflammatory drugs etc are more likely to induce liver damage in high risks groups that includes females, elderly and obese people. HLA halotype and variation in protein expression also plays an important role in this context. Various studies are available regarding clinical features, histopathological features, diagnosis and management related to antibiotics and acetaminophen induced liver damage. N acetylcysteine is commonly available antidote for drug induced hepatic damage. Role of other pharmacological agents as an antidote requires further studies. However, liver transplantation should be considered with drug induced lethal liver failure.